Effects of Fumarprotocetraric Acid, a Depsidone from the Lichen Cladonia verticillaris, on Tyrosinase Activity - Luiz Fabrício Gardini Brandão; Noemia Pereira da Silva Santos; Eugênia Cristina Gonçalves Pereira; Nicácio Henrique da Silva; Maria de Fatima Cepa Matos; Danielle Bogo; Neli Kika Honda (Orbital: The Electronic Journal of Chemistry, 2017)
Lichens are widely distributed around the world. Their phenolic compounds, consisting mainly of depsides and depsidones, have been extensively studied for important biological activities. More recently, these compounds have been evaluated for their inhibitory activity against enzymes such as tyrosinase, a key agent in melanin biosynthesis. In the present investigation, the depsidone fumarprotocetraric acid isolated from the lichen Cladonia verticillaris (Raddi) Fr. was evaluated for its inhibitory activity against this critical enzyme. Kinetic study showed that depsidone at 0.6 mM inhibited tyrosinase activity by 39.8%. Lineweaver–Burk plots revealed that fumarprotocetraric acid can act as an uncompetitive or mixed-type inhibitor, depending on concentration.DOI: http://dx.doi.org/10.17807/orbital.v9i4.999